Swearwords in Quentin Tarantino’s Movie, From Reservoir Dogs to Once Upon A Time in Hollywood - Sasa Maharani (TOTOBUANG, 2022)
Taboo is the prohibition or avoidance in any society of behavior believed to be harmful to its members in that it would cause them anxiety, embarrassment, or shame. Quentin Tarantino is one of the most well-known and respected directors of Hollywood films. He is also well known for creating films that are violent and vulgar. This research purpose is to analyze the use of ten popular swear words mentioned by Jay (2009) in ten films directed and written by Quentin Tarantino from Reservoir Dogs to Once Upon a Time in Hollywood. As a comparison, the Corpus of Contemporary American English (COCA) will be used to determine whether it has the same trends throughout the years. By using LancsBox to find the frequencies of the swear words, it is found that there are in total 1316 frequencies of nine swear words across the ten films. While the COCA graph tends to show significant growth in the use of swear words, in the Quentin Tarantino corpus it is shown that the graph tends to be unstable and has some significant decreases throughout the years. Keywords: swear words, corpus linguistics, sociolinguistics